Pengaruh Gaya Kepemimpinan Transformasional Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan PT Parkland World Indonesia Di Rangkasbitung - Syifah Fadhilah; Santi Octavianti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study examines the influence of transformational leadership style and physical work environment on employee performance at PT. Parkland World Indonesia di Rangkasbitung, both partially and simultaneously. A quantitative method with an asso-ciative approach was employed, involving a population of 1,260 employees and a sample of 93. Data analysis included validity tests, reliability tests, classical assump-tion tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. Results indicate that transformational leadership positively and sig-nificantly affects employee performance, with the regression equation Y = 23.666 + 0.539X1. The t-calculated value (4.556) exceeds t-table (1.98667), with significance < 0.05, rejecting H0 and accepting H1. The physical work environment also shows a positive and significant effect, with Y = 21.883 + 0.484X2; t-statistic (4.834) > t-table, significance < 0.05, rejecting H0 and accepting H2. Simultaneously, both factors posi-tively and significantly impact performance via Y = 17.617 + 0.319X1 + 0.326X2. The F-statistic (14.819) surpasses F-table (3.10), with significance 0.000 < 0.05, rejecting H0 and accepting H3. Recommendations include leaders serving as role models, im-proving lighting, and reevaluating work programs to enhance performance at PT. Parkland World Indonesia di Rangkasbitung